Evidence Based of Effects and Protection Mechanism of Lycium Barbarum Polysaccharide on Ethanol-Induced Liver Injury (Medico Legal Update, 2021)
Excessive ethanol intakes have been reported to be linked to liver diseases such as hepatitis and cancerrelated diseases of ethanol. Excessive ethanol can lead to the accumulation of reactive oxygen species(ROS) and to the depletion of glutathione (GSH) in the liver. Ethanol-induced oxidative stress substantiallyincreases peroxidation of the lipid and decreases GSH levels in human hepatocyte and animal models.Ethanol contributes to sterol regulating element-binding protein activation (SREBP)-1 by regulating maingenes such as Acetyl-CoA carboxylase (ACC) and Stearoyl-CoA desaturase 1(SCD1) to facilitate lipidaccumulation in the liver. The liquid fraction derived from wolfberry is lycium barbarum polysaccharide(LBP). In many animal disease models, it is an effective antioxidant and tissue protective agent. Researchershave shown hepato-protective functions in acute hepatic injury, NAFLDs, drugs-induced liver injury andhepatocellularcarcinoma models. The protection effect of L. barbarum polysaccharides (LBP) in this studyon ethanol-induced injury in human hepatocytes was explored. In addition, the influence of LBP on oxidativestress protein activity was examined.